Belgium : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper reviews Belgium's experience with fiscal adjustment and the long-term outlook for the public finances. The paper discusses the composition and scale of the fiscal adjustment, and the extent to which it has exerted a durable impact on the public finances. It offers a quantitative analysis of the interaction between fiscal policy and developments in saving and investment, with a view to contributing to reflection on desirable policy priorities in the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet